The The EFL Students' Experiences with Gamified Learning in Vocational Education: Automotive Students' Perspectives - Ranti, Merchandha Sovia; Degeng, Putu Dian Danayanti (ELLITE: Journal of English Language, Literature, and Teaching, 2025)
EFL instruction in vocational education faces challenges in student engagement and technological integration, as many vocational students prioritize major-related studies over English. To enhance engagement, gamification has been introduced as a learning strategy. This study employed a descriptive quantitative survey to explore vocational automotive students’ experiences with gamified learning. A total of 117 automotive students participated, using platforms such as Quizizz, Blooket, and Bamboozle. Data were collected through four Likert-scale questionnaires and analyzed in Microsoft Excel. The research aimed to answer three questions: (1) How does gamification influence students’ engagement in learning English in vocational high school? (2) How effective is gamification in improving students’ learning outcomes and motivation in English lessons? (3) What are students’ overall perceptions of using gamification in English lessons? Findings revealed that gamification significantly improved students' engagement, confidence, motivation, collaboration, and learning outcomes. Students also expressed strong support for its integration into other lessons. The study concludes that gamification is an effective method for enhancing English learning in vocational education. It is recommended that future research adopt a mixed-methods approach to gain deeper insights into vocational students’ experiences with gamified learning.